The relationship between leadership in BPM and company profitability - Dušan Gošnik; Maja Meško; Igor Stubelj (Administrative Sciences, 2023)
This paper studies the relationship between leadership as an activity of business process management (BPM) and company performance. Business process data about leadership and business processes in SMEs were collected via questionnaires on the population of 3007 SMEs in Slovenia. Aspects of leadership such as the involvement of employees, middle management, customers and suppliers were studied. The financial data of the SMEs of the sample were obtained from publicly available financial statements to assess relative residual income profitability ROEr and ROEa. Data analysis was performed using Bartlett's, Kaiser-Maier-Olkin and nonparametric Mann-Whitney U tests. We confirmed a positive relationship between employee involvement in leadership as an activity of BPM and company profitability. It was proved that companies that involve employees and middle management in improving core business processes to a greater degree are more profitable. Intense involvement of employees in changes in core business processes results in higher company profitability, which has been detected by the higher risk-adjusted profitability measure ROEa. Companies that involve middle management to a greater degree by leading employees based on their interests are more profitable. The results are important for managers as decision-makers and other company stakeholders, especially those responsible for business process improvements. Theoretical and practical implications and further research possibilities are discussed.
Keywords: 350; BPM; leadership; management; risk-adjusted profitability measures; SMEs